Growth and Survival of Ornate Spiny Lobster (Panulirus ornatus) in Nursery under Laboratory Condition (Philippine Journal of Agricultural Economics, 2017)
Nursery of juvenile lobsters in the coastal area was attempted but survival was very low with unknown causes of mortality. The study determined whether communal or individualized houses affect the growth and survival of small and big juvenile lobsters after 60 days nursery culture in the laboratory. Four (4) treatments with four (4) replicates were identified in Completely Randomized Design (CRD) and these were small juvenile lobsters in communal tank (T1), small juvenile lobsters in individualized tank (T2), big juvenile lobsters in communal tank (T3) and big juvenile lobsters in individualized tank (T4). Results showed that communal tank for big juveniles attained significantly (P